African traditional religion in the modern world - Thomas, Douglas E. (2015)
"The religious experiences of black people throughout the Americas are also covered. The author finds cosmology, symbolism and rituals of Yoruba culture to be the fundamental bases of African traditional religion, and draws similarities between the oral and written literature of West Africans and that of New World practitioners. The influence of Islam and Christianity is also discussed"--Provided by publisher.
The sacred role of culture in African religion -- African culture and western attitudes toward African religion -- African tradition and the culture of religion -- African culture and the philosophy of religion -- African religion in the New World -- Traditional African cultural forms in the Caribbean.
Includes bibliographical references and index.
Keywords: Christianity -- Influence; Islam -- Influence; Africa -- Religion